Personality and Cognitive Functions in Violent Offenders – Implications of Character Maturity? - Seidl, Helena; Nilsson, Thomas; Hofvander, Björn; Billstedt, Eva; Wallinius, Märta (Frontiers in Psychology, 2020)
Previous research has suggested that personality and cognitive functions are essential in the emergence of persistent aggressive antisocial behaviors and that character maturity could be an important protective factor against these behaviors. The aims of this study were (1) to determine associations between personality traits, intellectual ability, and executive function in young male violent offenders, and (2) to investigate differences in intellectual ability and executive function between groups of violent offenders with low, medium, and high character maturity. A cohort of 148 male violent offenders (18–25 years of age) participated in this study. The Temperament and Character Inventory was used as a self-report measure of personality traits, and cognitive functions were measured with the Wechsler Adult Intelligence Scale - Third Edition and the Cambridge Neuropsychological Test Automated Battery. Intellectual ability was negatively correlated to the temperament dimension Harm Avoidance and the character dimension Self-Transcendence, and positively correlated to the character dimensions Self-Directedness and Cooperativeness and the temperament dimension Novelty Seeking. Visual sustained attention correlated positively to the temperament dimension Persistence and negatively to the temperament dimension Harm Avoidance. Spatial working memory correlated negatively to the character dimension Cooperativeness. Character maturity, however, did not affect intellectual and executive functions to a statistically significant degree. Our findings indicate that offender personality characteristics such as optimism, responsibility, empathy, curiosity, and industry that would seem more favorable to positive intervention outcomes are related to better cognitive functioning. Possible implications are that interventions in offender populations could be more effective if tailored to participants’ personality dimensions and cognitive proficiencies, rather than offered as “one size fits all”.